TRADISI BAUSUNG PENGANTIN PADA BANJAR KANDANGAN DI KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Rahmah, Riska; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study analyzes the changes of the Bridal Bausung Tradition conducted in Tembilahan Sub-district, Indragiri Hilir District. By using qualitative methods with purposive sampling technique to determine the informant, the author determined 1 key informant and 5 informants to provide an explanation of the Bridal Bausung Tradition. The results of this study found that the Bausung tradition has undergone changes since the 80s. The changes here mean the changes in social systems which are found in the Bausung tradition such as changes in the time of implementation and equipment used. This tradition has sanctions if the offspring do not carry out the tradition of Bausung at Banjar traditional wedding ceremonies. This Bausung tradition is only carried out by the people of Banjar Kandangan descent. Banjar's customary wedding is clearly respect the bride and groom. Therefore, the bride and groom must be carried up, so that their position is higher than other people. Besides, the bride and groom are considered as the King and Queen (Raja dan Ratu Sahari) by the people of the Banjar descent. In addition, the bride and groom are also not allowed to set foot on the ground. Inheritance in the Bausung tradition is only inherited to boys, because it is already an initial provision. Whereas the woman can only carry out the tradition of Bausung because her father is obliged to pass on the tradition to her child, but later the woman cannot inherit this tradition even though she has a son.Â Keywords: Tradition, Bausung Social Changes